Dissolution of Parliament – Exercising or Abusing of Constitutional Authorizations - Orlović, Slobodan; Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Dissolution of parliament is a feature of a soft system of division of power. This constitutional institute is the most serious counterweight mechanism in relation to the instruments of parliamentary control of the government. Application of this institute, as a rule, presupposes an unresolved conflict in the relations between parliament and government. Hence the main purpose of this institute is to cut such a position that exists between parliament and government and to bring such a conflict to the citizens as the original holders of sovereignty. The first question that is opened in this paper is whether it is justifiable to use this institute in a situation of non-existence of serious conflict in relations between parliament and government, when government is supported by stable parliamentary majority. The second question that is opened in this paper is whether the act regarding the dissolution of parliament can be subject of legal control.